Dairy Business Analysis Project: 2003 Financial Summary - Albert de Vries; Russell Giesy; L. Ely; Brent Broaddus; C. Vann; B. Butler (EDIS)
This publication is a summary of the financial performance of Florida dairy businesses in the year 2003. It is intended for general use by dairy farmers, the allied industry, and government, and educational professionals. This document is DS178, one of a series of the Department of Animal Sciences, Florida Cooperative Extension Service, UF/IFAS. Published January 2005.